Risk and uncertainty assessment of natural disasters - Palková, Monika; Müllerová, Jana; Novák, Martin; Němec, Vladimír (SGEM, 2018)
The concepts of danger, uncertainty and risk are often used intuitively and inaccurately not only in common language but also in the media where it is unfortunately commonplace and last but not least in scientific circles. The clan defines uncertainty, danger and risk, and graphically visualises the aspects it encompasses. The graph is defined by two dimensions, namely probability and objectivity. The notion of danger is the least unequivocal. This is an object property that is a threat. Uncertainty was mathematically defined by Heisenberg, the Nobel Prize winner of physics. It demonstrates the existence of conjugated pair of physical quantities. The greater the certainty of the magnitude of one quantity simultaneously means the greater the uncertainty for determining the second quantity of the conjugated pair. Risk as a concept relates to the process of risk assessment and risk management. The risk is most often confused with danger or danger. The risk always applies to a particular object, group of objects, system or group of systems. For the complex risk assessment, RM/RA CRAMM has been recommended to allow for a truly comprehensive risk assessment in the selected area or a selective assessment of environmental, technological or social risks. The advantage of the method is the quantitative characteristic of the input and output variables and the simple comparison and thus the uniqueness of the results and the flexibility of the application in the change of the input conditions.
Hodnocení rizika a nejistot přírodních katastrof
Keywords: Risk management; education; Fire Rescue Service; analysis; Řízení rizik; vzdělání; Hasičská služba; analýza